Preparation method of cold-resistant and chemical-resistant high-impact polyphenylene sulfide special for new energy vehicles
Patent Information
- Application Number
- CN202610651052.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-05-12
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2046-05-12
AI Technical Summary
[0004]本发明的目的是提供一种新能源汽车专用的耐寒耐化学高冲击聚苯硫醚制备方法,解决现有聚苯硫醚复合材料中通过柔性增韧易损害耐化学性、通过提高结晶度或增强刚性连续相又易降低冲击韧性,以及通过强化玻璃纤维与基体之间的界面传力易在低温条件下加剧应力集中,从而难以同时兼顾耐寒性、耐化学性、高冲击和力学强度的技术问题
1.本发明通过在商品化长玻璃纤维表面依次构建硅氧烷锚定层和硅烷接枝聚苯硫醚层,形成由玻璃纤维表面向聚苯硫醚基体逐步过渡的梯度界面层,可降低界面突变引起的应力集中,提高界面传力效率与受冲击时的能量耗散能力,从而有利于聚苯硫醚制件获得较高冲击性能。
Smart Images

Figure CN122213683B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of polymer composite material preparation, specifically to a method for preparing cold-resistant, chemically resistant, and high-impact polyphenylene sulfide for new energy vehicles. Background Technology
[0002] As new energy vehicles evolve towards higher integration, lighter weight, and long-term service in complex environments, the working conditions of polyphenylene sulfide (PPS) components used for connection, support, isolation, and shell molding are becoming increasingly complex. During assembly and use, these PPS components must maintain high structural strength and dimensional stability while withstanding instantaneous impacts at low temperatures, alternating stresses caused by long-term vibrations, and stability requirements arising from contact with chemical media such as cooling and cleaning media. For long glass fiber reinforced PPS systems, the material not only needs good processability but also requires establishing a stable, non-brittle interface between commercially available long glass fibers and linear PPS resin to effectively transfer loads while avoiding excessive localized interface constraints that could increase the risk of low-temperature impact failure. Therefore, simultaneously achieving cold resistance, chemical resistance, high impact resistance, and mechanical support capabilities within the same PPS component has become a key requirement in the development of PPS materials for new energy vehicles.
[0003] Current research on glass fiber reinforced polyphenylene sulfide (PPS) commonly follows two routes: First, conventional treatment of the glass fiber surface using impregnating agents or silane coupling agents is employed. For example, Chinese patent CN101864169A discloses a glass fiber reinforced PPS resin composite material, focusing on achieving reinforcement through the composite of surface-treated glass fibers and PPS resin. Second, the introduction of additional toughening components and compatibilizers improves molding and impact performance. For instance, Chinese patent CN110776742A discloses a PPS composite material for high-filling, low-warpage battery module end plates and its preparation method, modifying the PPS system with glass fibers, glass microspheres, toughening agents, and compatibilizers. Based on the above disclosures and their technical focuses, existing solutions mostly optimize single paths of conventional interface reinforcement or multi-component blending toughening. While these can improve some strength, warpage, or impact issues, there is still room for improvement in the simultaneous coordination of stress relief under low-temperature conditions, interface stability and force transfer, matrix continuity and density, and chemical resistance. Summary of the Invention
[0004] The purpose of this invention is to provide a method for preparing cold-resistant, chemical-resistant, and high-impact polyphenylene sulfide (PPS) specifically for new energy vehicles. This method addresses the technical problems of existing PPS composite materials, where flexible toughening can easily compromise chemical resistance, increasing crystallinity or reinforcing the rigid continuous phase can easily reduce impact toughness, and strengthening the interfacial force transfer between glass fiber and the matrix can easily exacerbate stress concentration under low-temperature conditions. As a result, it is difficult to simultaneously achieve cold resistance, chemical resistance, high impact, and mechanical strength.
[0005] This invention does not simply add toughening components or simply strengthen the glass fiber interface. Instead, it first constructs a siloxane anchoring layer on the surface of commercially available long glass fibers, and then introduces silane-grafted polyphenylene sulfide to form an outer transition structure compatible with linear polyphenylene sulfide resin. This allows for the synergistic realization of interfacial force transfer, stress relief, and media barrier, thereby achieving a stable balance between cold resistance, chemical resistance, and high impact resistance.
[0006] To achieve the above objectives, the present invention provides the following technical solution: A method for preparing a cold-resistant, chemically resistant, and high-impact polyphenylene sulfide specifically for new energy vehicles includes the following steps: S1. Provides a silane-grafted polyphenylene sulfide, wherein the silane-grafted polyphenylene sulfide is obtained by grafting a linear polyphenylene sulfide resin with vinyltrimethoxysilane in the presence of dicumyl peroxide; S2. Provides 3-glycidoxypropyltrimethoxysilane hydrolysis treatment solution; S3. The commercial long glass fiber is treated with the 3-glycidoxypropyltrimethoxysilane hydrolysis treatment solution described in step S2, and then dried and cured to form a siloxane anchoring layer; then the long glass fiber with the siloxane anchoring layer is brought into contact with the silane-grafted polyphenylene sulfide described in step S1 to form a gradient interface layer on the surface of the commercial long glass fiber, thereby obtaining an interface-reinforced long glass fiber. S4. Directly melt-composite linear polyphenylene sulfide resin with the interface-reinforced long glass fiber, or first prepare preimpregnated long glass fiber polyphenylene sulfide granules, then melt-composite the preimpregnated long glass fiber polyphenylene sulfide granules with linear polyphenylene sulfide resin and granulate them to obtain a polyphenylene sulfide composition. S5. The polyphenylene sulfide composition obtained in step S4 is injection molded to obtain a polyphenylene sulfide part.
[0007] Furthermore, in step S1, the silane-grafted polyphenylene sulfide is prepared through the following steps: A1. Dry the linear polyphenylene sulfide resin at 120-140℃ for 3-6 hours; A2. The linear polyphenylene sulfide resin dried in step A1, vinyltrimethoxysilane, and dicumyl peroxide are mixed in a mass ratio of 100:0.5-8.0:0.05-1.0; A3. Under nitrogen protection, reactive extrusion is carried out at 290-310℃, screw speed of 100-300r / min, and residence time of 20-90s; A4. The extrudate is granulated and dried at 100-120℃ for 1-4h to obtain the silane-grafted polyphenylene sulfide.
[0008] Furthermore, in step S2, the 3-glycidoxypropyltrimethoxysilane hydrolysis solution is prepared through the following steps: B1. Mix 3-glycidoxypropyltrimethoxysilane, anhydrous ethanol and deionized water at a mass ratio of 100:300-1000:50-250; B2. Add glacial acetic acid to adjust the pH to 4.0-5.5; B3. Stir at 25-45℃ for 20-90 min to obtain the 3-glycidoxypropyltrimethoxysilane hydrolysis solution.
[0009] Furthermore, in step S3, the interface-reinforced long glass fiber is prepared through the following steps: C1. The commercially available long glass fiber is brought into contact with the 3-glycidoxypropyltrimethoxysilane hydrolysis treatment solution by spraying or dipping. C2. Dry at 110-140℃ for 10-40 min and cure at 140-170℃ for 5-20 min to form the siloxane anchoring layer; C3. The long glass fiber treated in step C2 is brought into contact with the silane-grafted polyphenylene sulfide at 290-315°C for 20-120 seconds to form the silane-grafted polyphenylene sulfide layer. C4. After cooling, the interface-reinforced long glass fiber is obtained, wherein the gradient interface layer, from the surface of the glass fiber outward, comprises a siloxane anchoring layer formed by the hydrolysis and condensation of 3-glycidoxypropyltrimethoxysilane and a silane-grafted polyphenylene sulfide layer formed by silane grafting polyphenylene sulfide. The thickness of the gradient interface layer is 50-300 nm, the amount of 3-glycidoxypropyltrimethoxysilane fixed is 0.20-1.20 wt%, and the amount of silane-grafted polyphenylene sulfide covering is 0.50-6.00 wt%, both based on the mass of commercially available long glass fiber.
[0010] Further, in step S4, before preparing the polyphenylene sulfide composition, prepreg long glass fiber polyphenylene sulfide granules are first prepared, and the prepreg long glass fiber polyphenylene sulfide granules are prepared through the following steps: D1. The linear polyphenylene sulfide resin is mixed with the interface-reinforced long glass fiber, wherein the linear polyphenylene sulfide resin accounts for 50-85 wt% and the interface-reinforced long glass fiber accounts for 15-50 wt%, with the total mass being 100 wt%; the mixture is melt-composited from the rear section of the barrel via a side-feed method in a twin-screw extruder at 300-320°C, a screw speed of 150-300 r / min, and a residence time of 20-60 s. D2. The discharged material is water-cooled and pelletized, and then dried at 120-140℃ for 2-6 hours to obtain the preimpregnated long glass fiber polyphenylene sulfide pellets.
[0011] Furthermore, in step S3, the nominal diameter of the commercially available long glass fiber is 10-17 μm; the length of the long glass fiber retained in the polyphenylene sulfide part obtained in step S5 is 0.25-0.80 mm.
[0012] Further, in step S4, the interface-reinforced long glass fiber or the pre-impregnated long glass fiber polyphenylene sulfide granules are fed from the rear section of the twin-screw extruder, located in the barrel section from L / 3 to L / 2 from the die head end, via a side-feed method, where L is the total effective length of the twin-screw extruder barrel.
[0013] Furthermore, the melt composite conditions in step S4 are as follows: barrel temperature is 300-320℃, screw speed is 150-300r / min, residence time is 20-60s, and vacuum exhaust is used.
[0014] Furthermore, the injection molding conditions in step S5 are: the injection molding machine barrel temperature is 315-330℃, the mold temperature is 140-160℃, and the injection speed is 30-120mm / s.
[0015] Furthermore, step S5 is followed by an annealing step, which is performed at 220-240°C for 15-40 minutes.
[0016] Furthermore, excluding glacial acetic acid, the mass fraction of 3-glycidoxypropyltrimethoxysilane in the 3-glycidoxypropyltrimethoxysilane hydrolysis treatment solution is 7.4-22.2 wt%, the volume fraction of anhydrous ethanol is not less than 99.5%, and the conductivity of deionized water is less than 5 μS / cm.
[0017] Furthermore, the preparation sequence of the 3-glycidoxypropyltrimethoxysilane hydrolysis treatment solution is as follows: first, 3-glycidoxypropyltrimethoxysilane is mixed with anhydrous ethanol to form a homogeneous system, then deionized water is added, followed by glacial acetic acid to adjust the acidity of the system, and the mixture is continuously stirred at 25-45℃ for 20-90 min; the glacial acetic acid is added dropwise at a rate of 0.5-2.0 mL / min, and the amount added is 0.2-3.0 wt% of the total mass of the mixture. The resulting hydrolysis treatment solution is a homogeneous liquid with no visible particles, no layering, and no visible gel.
[0018] Furthermore, the commercially available long glass fibers are from the same batch and have the same surface treatment state, and the original surface treatment agent retention state or removal state in the same embodiment remains consistent.
[0019] Furthermore, when commercially available long glass fibers come into contact with 3-glycidoxypropyltrimethoxysilane hydrolysis treatment solution, the spraying pressure under the spraying method is 0.2-0.8 MPa, the spraying distance is 10-30 cm, and the number of spraying times is 1-3; under the dip coating method, the immersion time is 10-120 s, the lifting speed is 5-50 mm / s, and the number of dip coating times is 1-2.
[0020] Furthermore, along the thickness direction away from the surface of the long glass fiber, the relative content of siloxane structural units in the gradient interface layer gradually decreases, while the relative content of silane-grafted polyphenylene sulfide segments gradually increases.
[0021] Furthermore, the amount of 3-glycidoxypropyltrimethoxysilane immobilized is expressed in wt%, calculated as the percentage of the difference in mass between the long glass fibers after forming the siloxane anchoring layer and the long glass fibers before treatment relative to the mass of the long glass fibers before treatment; the amount of silane-grafted polyphenylene sulfide coating is expressed in wt%, calculated as the percentage of the difference in mass between the long glass fibers after forming the silane-grafted polyphenylene sulfide layer and the long glass fibers after forming the siloxane anchoring layer relative to the mass of the long glass fibers before treatment.
[0022] Furthermore, the grafting degree of silane-grafted polyphenylene sulfide is the percentage of the total mass of the grafted silane structural units, and the silicon content is the mass fraction of silicon element. Before determining the grafting degree and silicon content, the silane-grafted polyphenylene sulfide is Soxhlet extracted with anhydrous ethanol or acetone at 50-80℃ for 6-24h to remove unreacted silane until the extract is clear and colorless. Then, it is vacuum dried at 100-120℃ to constant weight, and the silicon content is converted after elemental analysis or infrared spectroscopy quantitative determination.
[0023] Furthermore, when the long glass fiber forming the siloxane anchoring layer comes into contact with the silane-grafted polyphenylene sulfide, the silane-grafted polyphenylene sulfide is added in powder or granular form, with the amount added being 0.50-6.00 wt% to form a coating amount, and is melt-coated onto the surface of the long glass fiber at 290-315℃; the contact treatment is carried out using a high-speed mixer or a fluidized bed, with the high-speed mixer rotating at 50-200 r / min, the hot air flow rate in the fluidized bed being 0.5-2.0 m / s, and the treatment time being 20-120 s.
[0024] Furthermore, the Si-O-Si condensation bond between the siloxane anchoring layer and the silane-grafted polyphenylene sulfide layer was obtained by characterization after washing and drying the interface-reinforced long glass fibers. The washing solvent was anhydrous ethanol or acetone, and the washing temperature was 50-80℃. When acetone was used, the washing temperature was 50-56℃, and the washing was performed 3-5 times, each time for 30-60 minutes. The drying conditions were vacuum drying at 80-120℃ for 2-6 hours. Characterization methods included at least one of infrared spectroscopy, X-ray photoelectron spectroscopy, or solid-state NMR. Infrared spectroscopy was used to detect the fibers at a depth of 1000-1100 cm⁻¹. - ¹The characteristic absorption peaks of Si-O-Si within the range, or the 102-104 eV signal of Si2p detected in X-ray photoelectron spectroscopy.
[0025] Furthermore, the thickness of the gradient interface layer was determined by transmission electron microscopy observation of the cross-section of the interface-reinforced long glass fiber; the sample was prepared into an ultrathin section of 50-100 nm after being embedded in epoxy resin, at least 5 measurement points were uniformly selected in the circumference of each fiber, and at least 3 fibers were tested for each sample, and the arithmetic mean of all measurement points was used as the thickness of the gradient interface layer.
[0026] Furthermore, the ratio of linear polyphenylene sulfide resin to interface-reinforced long glass fiber is expressed as a mass ratio of 50-85:15-50, and when the total mass of the two is 100wt%, the linear polyphenylene sulfide resin accounts for 50-85wt% and the interface-reinforced long glass fiber accounts for 15-50wt%. The polyphenylene sulfide composition also includes one or more processing aids selected from antioxidants, lubricants, and release agents. The amount of processing aids added is calculated separately based on the total mass of the linear polyphenylene sulfide resin and the interface-reinforced long glass fiber.
[0027] Furthermore, interface-reinforced long glass fiber or pre-impregnated long glass fiber polyphenylene sulfide granules are fed from the last 1 / 3 to 1 / 2 of the barrel section of the twin-screw extruder via a side-feed method. The section is divided based on the total effective length of the twin-screw extruder barrel and with the die head side as the end.
[0028] Furthermore, the vacuum exhaust in the melt composite process is located in the exhaust section after the materials are melted and mixed, with a vacuum degree of -0.05 to -0.10 MPa.
[0029] Furthermore, nitrogen protection in reactive extrusion is achieved by purging the barrel with nitrogen before extrusion and continuously introducing nitrogen during the extrusion process.
[0030] Furthermore, the retained length of the long glass fibers was obtained by statistically analyzing the length distribution of the glass fibers after removing the polyphenylene sulfide resin matrix. The matrix removal method was to ignite at 500-600℃ for 2-4 hours, or to digest the matrix with a mixture of concentrated sulfuric acid and hydrogen peroxide at 80-100℃ for 30-60 minutes, followed by washing and drying. At least 200 glass fibers were randomly selected to measure their length, and the average length of the number of fibers was taken as the retained length.
[0031] As a concept of this invention, the present invention employs polyphenylene sulfide (PPS) constructed based on a gradient interface layer on the surface of commercially available long glass fibers. This is primarily used to achieve a synergistic balance between high impact performance and chemical resistance, as well as mechanical strength and cold resistance. In existing technologies, to improve mechanical strength and interfacial force transfer, the bonding between the glass fiber and the PPS matrix is typically strengthened directly, or the rigidity and crystallinity of the system are increased. However, such measures tend to enhance interfacial constraints, exacerbate low-temperature stress concentration, and make the continuous phase of the matrix more rigid, thus negatively impacting cold resistance and impact performance. Conversely, to improve low-temperature impact or toughness, flexible toughening structures or multiphase softening components are often introduced. However, this easily disrupts the continuous density of the PPS matrix, weakens chemical resistance, and affects the effective load transfer of the reinforced system. This invention first constructs a siloxane anchoring layer with 3-glycidoxypropyltrimethoxysilane, and then forms an outer layer compatible with linear polyphenylene sulfide resin by grafting polyphenylene sulfide with silane. A gradient interface layer is established between commercially available long glass fibers and the matrix, so that interface bonding, stress transition and compatibility coating are achieved simultaneously. This reduces the side effects of either single rigid reinforcement or single flexible toughening, and enables polyphenylene sulfide parts to maintain a more balanced overall performance under complex service conditions.
[0032] 3-Glycidoxypropyltrimethoxysilane focuses on forming a stable siloxane anchoring layer on the surface of commercially available long glass fibers, prioritizing the resolution of interfacial bonding and load transfer issues. However, if it acts alone or has an excessively high fixation level, the interface will exhibit strong inorganic and rigid characteristics, easily leading to stress concentration at low temperatures. Furthermore, its compatibility with linear polyphenylene sulfide resin is limited, making it difficult to balance impact resistance and cold resistance. Silane-grafted polyphenylene sulfide focuses on forming a similar segmental compatibility coating with linear polyphenylene sulfide resin, improving the continuity of the outer interfacial layer, stress relief, and media barrier. However, if it coats alone or has an excessively high coating level without the aforementioned anchoring foundation, it will insufficiently support the adhesion stability and interfacial durability of the commercially available long glass fiber surface, and the load transfer efficiency will also be limited. This invention achieves anchoring, compatibility, and transition compensation on the same interface by controlling the sequence of hydrolysis and condensation followed by melt coating, and by using a gradient interface layer composed of a siloxane anchoring layer and a silane-grafted polyphenylene sulfide layer, thereby taking into account interface strength, low-temperature impact resistance, and chemical stability.
[0033] Beneficial technical effects 1. This invention forms a gradient interface layer that gradually transitions from the glass fiber surface to the polyphenylene sulfide matrix by sequentially constructing a siloxane anchoring layer and a silane-grafted polyphenylene sulfide layer on the surface of commercially available long glass fibers. This reduces stress concentration caused by abrupt interface changes, improves interface force transmission efficiency and energy dissipation capacity under impact, and thus helps polyphenylene sulfide components obtain higher impact performance.
[0034] 2. This invention does not rely on a large proportion of flexible toughening phase, but uses silane-grafted polyphenylene sulfide that is compatible with linear polyphenylene sulfide resin to coat and transition the interface. While enhancing the stability of the interface, it maintains the continuity and compactness of the matrix, which helps to reduce the possibility of rapid penetration of chemical media along the interface. Therefore, it is more conducive to maintaining the chemical resistance of polyphenylene sulfide materials.
[0035] 3. By synergistically controlling the addition position of interface-reinforced long glass fibers, the melting and composite residence time, and the vacuum exhaust conditions, this invention can reduce excessive shearing of glass fibers and residual volatiles in the system while ensuring reinforcement efficiency. This is beneficial for retaining a longer effective length of glass fibers and stabilizing the molding process, thereby taking into account mechanical strength, molding stability, and part consistency.
[0036] 4. This invention moves the interface construction step forward to the commercial long glass fiber processing stage, and can be combined with the pre-impregnated long glass fiber polyphenylene sulfide granule path, so that the interface formation and subsequent melt composite work together. Under the conditions of low temperature use, chemical media contact and impact load, it is easier to maintain the balance of comprehensive performance, which is suitable for the preparation of polyphenylene sulfide parts for new energy vehicles. Attached Figure Description
[0037] Figure 1This is an XPS depth distribution map of the sample from Example 1.
[0038] Figure 2 This is the XPS depth distribution map of sample 8 (Comparative Example).
[0039] Figure 3 This is the XPS depth distribution map of the comparative sample 10.
[0040] Figure 4 This is a high-resolution peak fitting diagram of Si2p for the sample in Example 1.
[0041] Figure 5 This is a high-resolution peak fitting diagram of Si2p for Comparative Example 8.
[0042] Figure 6 This is a high-resolution peak fitting diagram of Si2p for Comparative Example 10.
[0043] Figure 7 The scatter plot shows the area ratio of Si components at the interface of the samples from Example 1, Comparative Example 8, and Comparative Example 10.
[0044] Figure 8 The ATR-FTIR spectra of the samples from Example 1, Comparative Example 9, and Comparative Example 10 after washing are shown.
[0045] Figure 9 Scatter plots of the characteristic peak area ratios of PPS / Si–O–Si for samples from Example 1, Comparative Example 9, and Comparative Example 10.
[0046] Figure 10 The diagram shows the probability density distribution of the long glass fiber lengths of the samples from Example 1 and Comparative Example 5.
[0047] Figure 11 Empirical CDF plots of the long glass fiber lengths for the samples of Example 1 and Comparative Example 5.
[0048] Figure 12 The image shows a two-dimensional correlation scatter plot of the impact-tensile strength at -40°C for samples from Example 1, Comparative Example 5, and Comparative Example 6.
[0049] Figure 13 The images show the DSC secondary heating curves of samples from Example 1, Comparative Example 7, and Comparative Example 10.
[0050] Figure 14 The following are DSC cooling curves of samples from Example 1, Comparative Example 7, and Comparative Example 10.
[0051] Figure 15 The above is a scatter plot of the apparent crystallinity of the samples from Example 1, Comparative Example 7, and Comparative Example 10.
[0052] Figure 16The graph shows the process curves of electrolyte immersion time versus tensile strength retention rate for samples from Example 1, Comparative Example 6, and Comparative Example 7.
[0053] Figure 17 The AUC scatter plot shows the retention area of the samples from Example 1, Comparative Example 6, and Comparative Example 7.
[0054] Figure 18 This is a macroscopic photograph of the polyphenylene sulfide sample from Example 1.
[0055] Figure 19 This is a scanning electron microscope (SEM) image of a cross-section of the polyphenylene sulfide (PPS) component from Example 1. Figure 19 Image a is a low-magnification scanning electron microscope (SEM) image of a cross-section of the polyphenylene sulfide (PPS) component from Example 1. Figure 19 Image b is a medium-magnification scanning electron microscope (SEM) image of a cross-section of the polyphenylene sulfide (PPS) component from Example 1. Figure 19 Image c is a high-magnification scanning electron microscope image of the cross-section of the polyphenylene sulfide sample from Example 1.
[0056] Figure 20 This is a bright-field transmission electron microscope (TEM) image of the cross-section of the interface-reinforced long glass fiber in Example 1. Detailed Implementation
[0057] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings.
[0058] Example 1 Step S1: Preparation of silane-grafted polyphenylene sulfide A1. Dry the linear polyphenylene sulfide resin at 120℃ for 3 hours.
[0059] A2. Mix 100 parts by weight of linear polyphenylene sulfide resin dried in step A1, 0.5 parts by weight of vinyltrimethoxysilane, and 0.05 parts by weight of dicumyl peroxide.
[0060] A3. Reactive extrusion was carried out under nitrogen protection at 290°C, screw speed of 100 r / min, and residence time of 20 s. Nitrogen protection was achieved by purging the barrel with nitrogen before extrusion and continuously introducing nitrogen during the extrusion process.
[0061] A4. The extrudate was pelleted and dried at 100°C for 1 hour to obtain the silane-grafted polyphenylene sulfide of this embodiment. The silane-grafted polyphenylene sulfide was extracted with anhydrous ethanol at 60°C for 12 hours to remove unreacted silane until the extract was clear and colorless, and then vacuum dried at 110°C to constant weight.
[0062] Step S2: Preparation of 3-glycidoxypropyltrimethoxysilane hydrolysis treatment solution B1. Mix 100 parts by mass of 3-glycidoxypropyltrimethoxysilane with 1000 parts by mass of anhydrous ethanol (volume fraction 99.5%) to form a homogeneous system, and then add 250 parts by mass of deionized water (conductivity less than 5 μS / cm).
[0063] Excluding glacial acetic acid, the mass fraction of 3-glycidoxypropyltrimethoxysilane is 100 / (100+1000+250)×100%=7.41wt%.
[0064] B2. Then add glacial acetic acid to adjust the pH to 4.0. Glacial acetic acid is added dropwise at a rate of 0.5 mL / min, and the amount added is 0.2 wt% of the total mass of the mixture.
[0065] B3. Stir at 25°C for 20 min to obtain the 3-glycidoxypropyltrimethoxysilane hydrolysis treatment solution of this embodiment, which is a homogeneous liquid with no visible particles, no layering and no visible gel.
[0066] Step S3: Preparation of interface-reinforced long glass fibers C1. Commercially available long glass fibers (nominal diameter 10 μm, from the same batch and with consistent surface treatment) are brought into contact with the 3-glycidoxypropyltrimethoxysilane hydrolysis treatment solution of this embodiment by dip coating. The immersion time is 10 s, the lifting speed is 5 mm / s, and the number of dip coatings is 1.
[0067] C2. Dry at 110°C for 10 min and cure at 140°C for 5 min to form the siloxane anchoring layer of this embodiment.
[0068] C3. The long glass fibers treated in step C2 are brought into contact with the silane-grafted polyphenylene sulfide of this embodiment at 290°C through a fluidized bed (hot air flow rate 0.5 m / s) for 20 s to form the silane-grafted polyphenylene sulfide layer of this embodiment. The silane-grafted polyphenylene sulfide is added in powder form, and the amount added is based on forming a coating of 0.50 wt%.
[0069] C4. After cooling, the interface-reinforced long glass fiber of this embodiment is obtained. The gradient interface layer of this embodiment includes, from the surface of the glass fiber outward, a siloxane anchoring layer formed by the hydrolysis and condensation of 3-glycidoxypropyltrimethoxysilane and a silane-grafted polyphenylene sulfide layer formed by silane grafting polyphenylene sulfide. The thickness of the gradient interface layer of this embodiment is 50 nm. The amount of 3-glycidoxypropyltrimethoxysilane fixed in this embodiment is 0.20 wt%, and the amount of silane-grafted polyphenylene sulfide covering in this embodiment is 0.50 wt%, both based on the mass of commercially available long glass fiber.
[0070] In this embodiment, along the thickness direction away from the surface of the long glass fiber, the relative content of siloxane structural units in the gradient interface layer gradually decreases, while the relative content of silane-grafted polyphenylene sulfide segments gradually increases.
[0071] In this embodiment, the Si-O-Si condensation bond between the siloxane anchoring layer and the silane-grafted polyphenylene sulfide layer in the interface-reinforced long glass fiber was characterized as follows: the fiber was washed three times with anhydrous ethanol at 50°C for 30 minutes each time, then vacuum-dried at 80°C for 2 hours. Infrared spectroscopy was used to detect the bond at 1000-1100 cm⁻¹. - ¹ Characteristic absorption peaks of Si-O-Si within the range.
[0072] In this embodiment, the thickness of the gradient interface layer was determined by transmission electron microscopy observation of the cross-section of the interface-reinforced long glass fiber. The sample was prepared by embedding it in epoxy resin and then preparing an ultrathin section of 50 nm. At least 5 measurement points were uniformly selected in the circumference of each fiber, and at least 3 fibers were tested for each sample. The arithmetic mean of all measurement points was used as the thickness of the gradient interface layer.
[0073] Step S4: Preparation of polyphenylene sulfide composition 85 parts by weight of linear polyphenylene sulfide resin and 15 parts by weight of interface-reinforced long glass fiber in this embodiment are directly melt-composite. In this embodiment, the interface-reinforced long glass fiber is added from the rear section of the twin-screw extruder at a distance of L / 3 from the die head end via side feeding, where L is the total effective length of the twin-screw extruder barrel.
[0074] The melt-compositing conditions are as follows: barrel temperature 300℃, screw speed 150 r / min, residence time 20 s, and vacuum exhaust. Vacuum exhaust is located in the exhaust section after the material is melted and mixed, with a vacuum degree of -0.05 MPa.
[0075] Water-cooled pelletizing yields the polyphenylene sulfide composition of this embodiment. In this embodiment, the mass ratio of linear polyphenylene sulfide resin to interface-reinforced long glass fiber in the polyphenylene sulfide composition is 85:15, meaning that when the total mass of both is 100 wt%, the linear polyphenylene sulfide resin accounts for 85 wt% and the interface-reinforced long glass fiber accounts for 15 wt%. This embodiment's polyphenylene sulfide composition also includes 0.3 wt% antioxidant and 0.2 wt% lubricant.
[0076] Step S5: Injection Molding The polyphenylene sulfide composition of this embodiment was injection molded at a barrel temperature of 315°C, a mold temperature of 140°C, and an injection speed of 30 mm / s (characterized by the forward movement speed of the injection molding machine screw) to obtain the polyphenylene sulfide part of this embodiment.
[0077] Annealing The polyphenylene sulfide part of this embodiment was annealed at 220°C for 15 minutes.
[0078] Performance Characterization In this embodiment, the retained length of the long glass fibers in the polyphenylene sulfide (PPS) component is 0.25 mm. The retained length of the long glass fibers was obtained by statistically analyzing the length distribution of the glass fibers after removing the PPS resin matrix. The matrix was removed by digesting the fiber with a mixture of concentrated sulfuric acid and hydrogen peroxide at 80°C for 30 minutes, followed by washing and drying. At least 200 glass fibers were randomly selected to measure their length, and the average length of the selected fibers was taken as the retained length.
[0079] Features of this embodiment: This embodiment employs a scheme where the ratio of grafted monomers to initiators is within the low range. The reaction extrusion temperature is selected towards the lower limit, and the screw speed and residence time are also within the low range, resulting in a low degree of silane grafting. This embodiment adopts a conservative low-parameter configuration overall, suitable for cost-sensitive applications with high processing performance requirements, such as automotive interior parts and electrical appliance housings—components that do not require high strength but need good flowability.
[0080] Example 2 Step S1: Preparation of silane-grafted polyphenylene sulfide A1. Dry the linear polyphenylene sulfide resin at 140℃ for 6 hours.
[0081] A2. Mix 100 parts by weight of linear polyphenylene sulfide resin dried in step A1, 8.0 parts by weight of vinyltrimethoxysilane, and 1.0 parts by weight of dicumyl peroxide.
[0082] A3. Reactive extrusion was carried out under nitrogen protection at 310°C, screw speed of 300 r / min, and residence time of 90 s. Nitrogen protection was achieved by purging the barrel with nitrogen before extrusion and continuously introducing nitrogen during the extrusion process.
[0083] A4. The extrudate was pelleted and dried at 120°C for 4 hours to obtain the silane-grafted polyphenylene sulfide of this embodiment. The silane-grafted polyphenylene sulfide was extracted with acetone at 56°C using a Soxhlet extract for 24 hours to remove unreacted silane until the extract was clear and colorless, and then vacuum dried at 120°C to constant weight.
[0084] Step S2: Preparation of 3-glycidoxypropyltrimethoxysilane hydrolysis treatment solution B1. Mix 100 parts by mass of 3-glycidoxypropyltrimethoxysilane with 300 parts by mass of anhydrous ethanol (volume fraction 99.5%) to form a homogeneous system, and then add 50 parts by mass of deionized water (conductivity less than 5 μS / cm).
[0085] Excluding glacial acetic acid, the mass fraction of 3-glycidoxypropyltrimethoxysilane is 100 / (100+300+50)×100%=22.22wt%.
[0086] B2. Then add glacial acetic acid to adjust the pH to 5.5. Glacial acetic acid is added dropwise at a rate of 2.0 mL / min, and the amount added is 3.0 wt% of the total mass of the mixture.
[0087] B3. Stir at 45°C for 90 min to obtain the 3-glycidoxypropyltrimethoxysilane hydrolysis treatment solution of this embodiment, which is a homogeneous liquid with no visible particles, no layering and no visible gel.
[0088] Step S3: Preparation of interface-reinforced long glass fibers C1. Commercially available long glass fibers (nominal diameter 17μm, from the same batch and with consistent surface treatment) are brought into contact with the 3-glycidoxypropyltrimethoxysilane hydrolysis treatment solution of this embodiment by spraying. The spraying pressure is 0.8MPa, the spraying distance is 30cm, and the number of spraying times is 3.
[0089] C2. Dry at 140°C for 40 min and cure at 170°C for 20 min to form the siloxane anchoring layer of this embodiment.
[0090] C3. The long glass fibers treated in step C2 are brought into contact with the silane-grafted polyphenylene sulfide of this embodiment at 315°C for 120 seconds using a high-speed mixer (200 r / min) to form the silane-grafted polyphenylene sulfide layer of this embodiment. The silane-grafted polyphenylene sulfide is added in granular form, and the amount added is based on forming a coating of 6.00 wt%.
[0091] C4. After cooling, the interface-reinforced long glass fiber of this embodiment is obtained. The gradient interface layer of this embodiment includes, from the surface of the glass fiber outward, a siloxane anchoring layer formed by the hydrolysis and condensation of 3-glycidoxypropyltrimethoxysilane and a silane-grafted polyphenylene sulfide layer formed by silane grafting polyphenylene sulfide. The thickness of the gradient interface layer of this embodiment is 300 nm. The amount of 3-glycidoxypropyltrimethoxysilane fixed in this embodiment is 1.20 wt%, and the amount of silane-grafted polyphenylene sulfide covering in this embodiment is 6.00 wt%, both based on the mass of commercially available long glass fiber.
[0092] In this embodiment, along the thickness direction away from the surface of the long glass fiber, the relative content of siloxane structural units in the gradient interface layer gradually decreases, while the relative content of silane-grafted polyphenylene sulfide segments gradually increases.
[0093] In this embodiment, the Si-O-Si condensation connection between the siloxane anchoring layer and the silane-grafted polyphenylene sulfide layer in the interface-reinforced long glass fiber was characterized as follows: the fiber was washed five times with acetone at 56°C for 60 min each time, and then vacuum dried at 120°C for 6 h. The Si2p signal of 102-104 eV was detected by X-ray photoelectron spectroscopy.
[0094] In this embodiment, the thickness of the gradient interface layer was determined by transmission electron microscopy observation of the cross-section of the interface-reinforced long glass fiber. The sample was prepared by embedding it in epoxy resin and then preparing an ultrathin section of 100 nm. At least 5 measurement points were uniformly selected in the circumference of each fiber, and at least 3 fibers were tested for each sample. The arithmetic mean of all measurement points was used as the thickness of the gradient interface layer.
[0095] Step S4: Preparation of polyphenylene sulfide composition 50 parts by weight of linear polyphenylene sulfide resin and 50 parts by weight of interface-reinforced long glass fiber in this embodiment are directly melt-composite. In this embodiment, the interface-reinforced long glass fiber is added from the rear section of the twin-screw extruder at a distance L / 2 from the die head end via side feeding, where L is the total effective length of the twin-screw extruder barrel.
[0096] The melt-compositing conditions are as follows: barrel temperature 320℃, screw speed 300 r / min, residence time 60 s, and vacuum exhaust. Vacuum exhaust is located in the exhaust section after the materials have melted and mixed, with a vacuum level of -0.10 MPa.
[0097] Water-cooled pelletizing yields the polyphenylene sulfide composition of this embodiment. In this embodiment, the mass ratio of linear polyphenylene sulfide resin to interface-reinforced long glass fibers in the polyphenylene sulfide composition is 50:50, meaning that when the total mass of both is 100 wt%, the linear polyphenylene sulfide resin accounts for 50 wt% and the interface-reinforced long glass fibers account for 50 wt%. This embodiment's polyphenylene sulfide composition also includes 0.5 wt% antioxidant, 0.3 wt% lubricant, and 0.2 wt% mold release agent.
[0098] Step S5: Injection Molding The polyphenylene sulfide composition of this embodiment was injection molded at a barrel temperature of 330°C, a mold temperature of 160°C, and an injection speed of 120 mm / s (characterized by the forward movement speed of the injection molding machine screw) to obtain the polyphenylene sulfide part of this embodiment.
[0099] Annealing The polyphenylene sulfide part of this embodiment was annealed at 240°C for 40 minutes.
[0100] Performance Characterization In this embodiment, the retained length of the long glass fibers in the polyphenylene sulfide (PPS) component is 0.80 mm. The retained length of the long glass fibers was obtained by statistically analyzing the length distribution of the glass fibers after removing the PPS resin matrix. The matrix removal method was to ignite at 600°C for 4 hours, followed by washing and drying. At least 200 glass fibers were randomly selected to measure their length, and the average length of the selected fibers was taken as the retained length.
[0101] Features of this embodiment: This embodiment employs a scheme with the grafted monomer and initiator ratios within the high range, and the reaction extrusion temperature is selected towards the upper limit, while the screw speed and residence time are also within the high range, resulting in a high degree of silane grafting. The overall configuration utilizes reinforced high parameters, forming a thick and dense interfacial layer with high interfacial bonding strength. This is suitable for applications with extremely high mechanical performance requirements, such as new energy vehicle power battery trays, chassis structural components, and high-voltage electrical connectors—critical components that need to withstand extreme low temperatures and chemical corrosion environments.
[0102] Example 3 Step S1: Preparation of silane-grafted polyphenylene sulfide A1. Dry the linear polyphenylene sulfide resin at 130℃ for 4 hours.
[0103] A2. Mix 100 parts by weight of linear polyphenylene sulfide resin dried in step A1, 4.0 parts by weight of vinyltrimethoxysilane, and 0.5 parts by weight of dicumyl peroxide.
[0104] A3. Reactive extrusion was carried out under nitrogen protection at 300°C, screw speed of 200 r / min, and residence time of 55 s. Nitrogen protection was achieved by purging the barrel with nitrogen before extrusion and continuously introducing nitrogen during the extrusion process.
[0105] A4. The extrudate was granulated and dried at 110°C for 2 hours to obtain the silane-grafted polyphenylene sulfide of this embodiment. The silane-grafted polyphenylene sulfide was extracted with anhydrous ethanol at 65°C for 15 hours to remove unreacted silane until the extract was clear and colorless, and then vacuum dried at 110°C to constant weight.
[0106] Step S2: Preparation of 3-glycidoxypropyltrimethoxysilane hydrolysis treatment solution B1. Mix 100 parts by mass of 3-glycidoxypropyltrimethoxysilane with 650 parts by mass of anhydrous ethanol (99.5% by volume) to form a homogeneous system, and then add 150 parts by mass of deionized water (conductivity less than 5 μS / cm).
[0107] Excluding glacial acetic acid, the mass fraction of 3-glycidoxypropyltrimethoxysilane is 100 / (100+650+150)×100%=11.11wt%.
[0108] B2. Then add glacial acetic acid to adjust the pH to 4.8. Glacial acetic acid is added dropwise at a rate of 1.2 mL / min, and the amount added is 1.5 wt% of the total mass of the mixture.
[0109] B3. Stir at 35°C for 55 min to obtain the 3-glycidoxypropyltrimethoxysilane hydrolysis treatment solution of this embodiment, which is a homogeneous liquid with no visible particles, no layering and no visible gel.
[0110] Step S3: Preparation of interface-reinforced long glass fibers C1. Commercially available long glass fibers (nominal diameter 13μm, from the same batch and with consistent surface treatment) are brought into contact with the 3-glycidoxypropyltrimethoxysilane hydrolysis treatment solution of this embodiment by dip coating. The immersion time is 60s, the lifting speed is 25mm / s, and the number of dip coatings is 2.
[0111] C2. Dry at 125°C for 25 min and cure at 155°C for 12 min to form the siloxane anchoring layer of this embodiment.
[0112] C3. The long glass fibers treated in step C2 are brought into contact with the silane-grafted polyphenylene sulfide of this embodiment at 302°C through a fluidized bed (hot air flow rate 1.2 m / s) for 70 s to form the silane-grafted polyphenylene sulfide layer of this embodiment. The silane-grafted polyphenylene sulfide is added in powder form, and the amount added is based on forming a coating of 3.0 wt%.
[0113] C4. After cooling, the interface-reinforced long glass fiber of this embodiment is obtained. The gradient interface layer of this embodiment includes, from the surface of the glass fiber outward, a siloxane anchoring layer formed by the hydrolysis and condensation of 3-glycidoxypropyltrimethoxysilane and a silane-grafted polyphenylene sulfide layer formed by silane grafting polyphenylene sulfide. The thickness of the gradient interface layer of this embodiment is 175 nm. The amount of 3-glycidoxypropyltrimethoxysilane fixed in this embodiment is 0.70 wt%, and the amount of silane-grafted polyphenylene sulfide covering in this embodiment is 3.0 wt%, both based on the mass of commercially available long glass fiber.
[0114] In this embodiment, along the thickness direction away from the surface of the long glass fiber, the relative content of siloxane structural units in the gradient interface layer gradually decreases, while the relative content of silane-grafted polyphenylene sulfide segments gradually increases.
[0115] In this embodiment, the Si-O-Si condensation bond between the siloxane anchoring layer and the silane-grafted polyphenylene sulfide layer in the interface-reinforced long glass fiber was characterized as follows: the fiber was washed four times with anhydrous ethanol at 65°C for 45 min each time, then vacuum-dried at 100°C for 4 h. Infrared spectroscopy was used to detect the bond at 1000-1100 cm⁻¹.- ¹ Characteristic absorption peaks of Si-O-Si within the range.
[0116] In this embodiment, the thickness of the gradient interface layer was determined by transmission electron microscopy observation of the cross-section of the interface-reinforced long glass fiber. The sample was prepared by embedding it in epoxy resin and then preparing an ultrathin section of 75 nm. At least 5 measurement points were uniformly selected in the circumference of each fiber, and at least 3 fibers were tested for each sample. The arithmetic mean of all measurement points was used as the thickness of the gradient interface layer.
[0117] Step S4: Preparation of polyphenylene sulfide composition First, pre-impregnated long glass fiber polyphenylene sulfide granules are prepared: D1. 67 parts by weight of linear polyphenylene sulfide resin and 33 parts by weight of interface-reinforced long glass fiber of this embodiment are melt-composite in a twin-screw extruder at 310°C, screw speed of 225 r / min and residence time of 40 s, from the rear section of the barrel via a side-feed method.
[0118] D2. The discharged material is water-cooled and pelletized, and then dried at 130°C for 4 hours to obtain the prepreg long glass fiber polyphenylene sulfide pellets of this embodiment.
[0119] Further preparation of polyphenylene sulfide composition: In this embodiment, 100 parts by weight of prepreg long glass fiber polyphenylene sulfide granules and 42 parts by weight of linear polyphenylene sulfide resin are melt-composite and granulated. In this embodiment, the prepreg long glass fiber polyphenylene sulfide granules are fed from the rear section of the twin-screw extruder at a distance of 2L / 5 from the die head end via side feeding, where L is the total effective length of the twin-screw extruder barrel.
[0120] The melt-compositing conditions were as follows: barrel temperature 310℃, screw speed 225 r / min, residence time 40 s, and vacuum exhaust. Vacuum exhaust was located in the exhaust section after the materials were melt-mixed, with a vacuum level of -0.075 MPa.
[0121] Water-cooled pelletizing yields the polyphenylene sulfide composition of this embodiment. In this embodiment, the mass ratio of linear polyphenylene sulfide resin to interface-reinforced long glass fiber in the polyphenylene sulfide composition is approximately 76.8:23.2, meaning that when the total mass of both is 100 wt%, the linear polyphenylene sulfide resin accounts for approximately 76.8 wt% and the interface-reinforced long glass fiber accounts for approximately 23.2 wt%. Furthermore, based on the total mass of the two components, the polyphenylene sulfide composition of this embodiment also includes 0.4 wt% antioxidant and 0.25 wt% lubricant.
[0122] Step S5: Injection Molding The polyphenylene sulfide composition of this embodiment was injection molded at a barrel temperature of 322°C, a mold temperature of 150°C, and an injection speed of 75 mm / s (characterized by the forward movement speed of the injection molding machine screw) to obtain the polyphenylene sulfide part of this embodiment.
[0123] Annealing The polyphenylene sulfide part of this embodiment was annealed at 230°C for 27 minutes.
[0124] Performance Characterization In this embodiment, the retained length of the long glass fibers in the polyphenylene sulfide (PPS) component is 0.53 mm. The retained length of the long glass fibers was obtained by statistically analyzing the length distribution of the glass fibers after removing the PPS resin matrix. The matrix was removed by digesting the fiber with a mixture of concentrated sulfuric acid and hydrogen peroxide at 90°C for 45 min, followed by washing and drying. At least 200 glass fibers were randomly selected to measure their length, and the average length of the selected fibers was taken as the retained length.
[0125] Features of this embodiment: This embodiment employs a two-step process, achieving uniform dispersion of glass fiber through pre-impregnated granule preparation followed by dilution. The ratios of grafted monomers and initiators are selected to be moderate, as are the parameters of the hydrolysis treatment solution, the amount of interfacial layer fixation, and the amount of coating. The key feature of this embodiment is its balanced parameter configuration, balancing cost and performance. It is suitable for applications under standard operating conditions, such as battery pack housings, motor housings, and charging pile housings for new energy vehicles—components requiring a balance between mechanical properties, chemical resistance, and cost. The final glass fiber content is 23%, a moderate ratio that meets the mechanical performance requirements of most new energy vehicle components.
[0126] Example 4 Step S1: Preparation of silane-grafted polyphenylene sulfide A1. Dry the linear polyphenylene sulfide resin at 125℃ for 5 hours.
[0127] A2. Mix 100 parts by weight of linear polyphenylene sulfide resin dried in step A1, 2.5 parts by weight of vinyltrimethoxysilane, and 0.3 parts by weight of dicumyl peroxide.
[0128] A3. Reactive extrusion was carried out under nitrogen protection at 295°C, screw speed of 180 r / min, and residence time of 65 s. Nitrogen protection was achieved by purging the barrel with nitrogen before extrusion and continuously introducing nitrogen during the extrusion process.
[0129] A4. The extrudate was pelleted and dried at 105°C for 3 hours to obtain the silane-grafted polyphenylene sulfide of this embodiment. The silane-grafted polyphenylene sulfide was extracted with anhydrous ethanol at 70°C for 18 hours to remove unreacted silane until the extract was clear and colorless, and then vacuum dried at 105°C to constant weight.
[0130] Step S2: Preparation of 3-glycidoxypropyltrimethoxysilane hydrolysis treatment solution B1. Mix 100 parts by mass of 3-glycidoxypropyltrimethoxysilane with 450 parts by mass of anhydrous ethanol (99.5% by volume) to form a homogeneous system, and then add 80 parts by mass of deionized water (conductivity less than 5 μS / cm).
[0131] Excluding glacial acetic acid, the mass fraction of 3-glycidoxypropyltrimethoxysilane is 100 / (100+450+80)×100%=15.87wt%.
[0132] B2. Then add glacial acetic acid to adjust the pH to 4.6. Glacial acetic acid is added dropwise at a rate of 1.5 mL / min, and the amount added is 2.0 wt% of the total mass of the mixture.
[0133] B3. Stir at 30°C for 65 min to obtain the 3-glycidoxypropyltrimethoxysilane hydrolysis treatment solution of this embodiment, which is a homogeneous liquid with no visible particles, no layering and no visible gel.
[0134] Step S3: Preparation of interface-reinforced long glass fibers C1. Commercially available long glass fibers (nominal diameter 14μm, from the same batch and with consistent surface treatment) are brought into contact with the 3-glycidoxypropyltrimethoxysilane hydrolysis treatment solution of this embodiment by spraying. The spraying pressure is 0.2MPa, the spraying distance is 10cm, and the number of spraying times is 1.
[0135] C2. Dry at 120°C for 30 min and cure at 150°C for 15 min to form the siloxane anchoring layer of this embodiment.
[0136] C3. The long glass fibers treated in step C2 are brought into contact with the silane-grafted polyphenylene sulfide of this embodiment at 295°C for 100 seconds using a high-speed mixer (50 r / min) to form the silane-grafted polyphenylene sulfide layer of this embodiment. The silane-grafted polyphenylene sulfide is added in powder form, and the amount added is based on forming a coating of 2.5 wt%.
[0137] C4. After cooling, the interface-reinforced long glass fiber of this embodiment is obtained. The gradient interface layer of this embodiment includes, from the surface of the glass fiber outward, a siloxane anchoring layer formed by the hydrolysis and condensation of 3-glycidoxypropyltrimethoxysilane and a silane-grafted polyphenylene sulfide layer formed by silane grafting polyphenylene sulfide. The thickness of the gradient interface layer of this embodiment is 200 nm. The amount of 3-glycidoxypropyltrimethoxysilane fixed in this embodiment is 0.85 wt%, and the amount of silane-grafted polyphenylene sulfide covering in this embodiment is 2.5 wt%, both based on the mass of commercially available long glass fiber.
[0138] In this embodiment, along the thickness direction away from the surface of the long glass fiber, the relative content of siloxane structural units in the gradient interface layer gradually decreases, while the relative content of silane-grafted polyphenylene sulfide segments gradually increases.
[0139] In this embodiment, the Si-O-Si condensation connection between the siloxane anchoring layer and the silane-grafted polyphenylene sulfide layer in the interface-reinforced long glass fiber was characterized as follows: the fiber was washed three times with acetone at 70°C for 50 min each time, and then vacuum dried at 110°C for 5 h. The Si2p signal of 102-104 eV was detected by X-ray photoelectron spectroscopy.
[0140] In this embodiment, the thickness of the gradient interface layer was determined by transmission electron microscopy observation of the cross-section of the interface-reinforced long glass fiber. The sample was prepared by embedding it in epoxy resin and then preparing an ultrathin section of 65 nm. At least 5 measurement points were uniformly selected in the circumference of each fiber, and at least 3 fibers were tested for each sample. The arithmetic mean of all measurement points was used as the thickness of the gradient interface layer.
[0141] Step S4: Preparation of polyphenylene sulfide composition First, pre-impregnated long glass fiber polyphenylene sulfide granules are prepared: D1. 55 parts by weight of linear polyphenylene sulfide resin and 45 parts by weight of interface-reinforced long glass fiber of this embodiment are melt-composite in a twin-screw extruder at 305°C, screw speed of 180 r / min and residence time of 50 s, from the rear section of the barrel via a side-feed method.
[0142] D2. The discharged material is water-cooled and pelletized, and then dried at 120°C for 2 hours to obtain the prepreg long glass fiber polyphenylene sulfide pellets of this embodiment.
[0143] Further preparation of polyphenylene sulfide composition: In this embodiment, 100 parts by weight of prepreg long glass fiber polyphenylene sulfide granules and 85 parts by weight of linear polyphenylene sulfide resin are melt-composite and granulated. In this embodiment, the prepreg long glass fiber polyphenylene sulfide granules are fed from the rear section of the twin-screw extruder at a distance of L / 3 from the die head end via side feeding, where L is the total effective length of the twin-screw extruder barrel.
[0144] The melt-compositing conditions were: barrel temperature 305℃, screw speed 180 r / min, residence time 50 s, and vacuum exhaust. Vacuum exhaust was located in the exhaust section after the materials were melt-mixed, with a vacuum level of -0.06 MPa.
[0145] Water-cooled pelletizing yields the polyphenylene sulfide composition of this embodiment. In this embodiment, the mass ratio of linear polyphenylene sulfide resin to interface-reinforced long glass fibers in the polyphenylene sulfide composition is approximately 75.7:24.3, meaning that when the total mass of both is 100 wt%, the linear polyphenylene sulfide resin accounts for approximately 75.7 wt% and the interface-reinforced long glass fibers account for approximately 24.3 wt%. Furthermore, based on the total mass of the two components, the polyphenylene sulfide composition of this embodiment also includes 0.35 wt% antioxidant and 0.15 wt% release agent.
[0146] Step S5: Injection Molding The polyphenylene sulfide composition of this embodiment was injection molded at a barrel temperature of 318°C, a mold temperature of 145°C, and an injection speed of 45 mm / s (characterized by the forward movement speed of the injection molding machine screw) to obtain the polyphenylene sulfide part of this embodiment.
[0147] Annealing The polyphenylene sulfide part of this embodiment was annealed at 225°C for 35 minutes.
[0148] Performance Characterization In this embodiment, the retained length of the long glass fibers in the polyphenylene sulfide (PPS) component is 0.62 mm. The retained length of the long glass fibers was obtained by statistically analyzing the length distribution of the glass fibers after removing the PPS matrix. The matrix removal method was to ignite at 520°C for 2 hours, followed by washing and drying. At least 200 glass fibers were randomly selected to measure their length, and the average length of the selected fibers was taken as the retained length.
[0149] Features of this embodiment: This embodiment employs a two-step process route. The ratio of grafted monomers and initiator, the parameters of the hydrolysis treatment solution, and the interface layer parameters are all selected at moderately low values. The spraying pressure, spraying distance, and high-speed mixer speed are all within the low-range range. The characteristic of this embodiment is its use of moderately conservative parameter configuration, balancing cost control with basic performance requirements. It is suitable for cost-sensitive applications requiring certain mechanical properties, such as auxiliary components like charging interface housings for new energy vehicles, wiring harness protective covers, and sensor brackets. The final glass fiber content is 24%, a moderate ratio that meets the mechanical performance and chemical resistance requirements of most auxiliary components.
[0150] Comparative Example 1: It is basically the same as Example 1, except that in step S2, after adding glacial acetic acid, the pH value of the 3-glycidoxypropyltrimethoxysilane hydrolysis treatment solution is adjusted to 6.0, and it is stirred at 25°C for 20 min, while other conditions remain unchanged.
[0151] Comparative Example 2: Basically the same as Example 1, except that in step S2, the mass ratio of 3-glycidoxypropyltrimethoxysilane, anhydrous ethanol and deionized water was changed to 100:250:50. The mass fraction of 3-glycidoxypropyltrimethoxysilane was 25.00 wt% when glacial acetic acid was not included. Then, glacial acetic acid was added at a dropping rate of 0.5 mL / min to adjust the pH to 4.0, and the mixture was stirred at 25 °C for 20 min, while other conditions remained unchanged.
[0152] Comparative Example 3: It is basically the same as Example 1, except that the curing conditions in step S3 are changed to curing at 130°C for 5 minutes, the drying conditions are still at 110°C for 10 minutes, and other conditions remain unchanged.
[0153] Comparative Example 4: It is basically the same as Example 1, except that in step S3, the contact temperature between the long glass fiber treated in step C2 and the silane-grafted polyphenylene sulfide is changed to 280°C, the contact time is still 20s, the fluidized bed hot air flow rate is still 0.5m / s, and other conditions remain unchanged.
[0154] Comparative Example 5: It is basically the same as Example 1, except that in step S4, the interface-reinforced long glass fiber and linear polyphenylene sulfide resin are simultaneously added from the main feed port of the twin-screw extruder for melt composite, instead of being added from the last 1 / 3 of the barrel section of the twin-screw extruder via side feeding. Other conditions remain unchanged.
[0155] Comparative Example 6: It is basically the same as Example 1, except that the vacuum exhaust is cancelled in the melt composite process of step S4, the exhaust section is kept at normal pressure, and other conditions remain unchanged.
[0156] Comparative Example 7: Basically the same as Example 1, except that no annealing is performed after step S5, and other conditions remain unchanged.
[0157] Comparative Example 8: Essentially the same as Example 1, except that in step S3, the commercially available long glass fibers were not treated with the 3-glycidoxypropyltrimethoxysilane hydrolysis solution. Instead, the commercially available long glass fibers, untreated in steps C1 and C2, were directly contacted with the silane-grafted polyphenylene sulfide from Example 1 in a fluidized bed at 290°C for 20 seconds, allowing the silane-grafted polyphenylene sulfide to coat the fiber surface at a coating amount of 0.50 wt%. Other conditions remained unchanged. This comparative example was used to verify the synergistic effect of the siloxane anchoring layer and the silane-grafted polyphenylene sulfide layer.
[0158] Comparative Example 9: Essentially the same as Example 1, except that after the 3-glycidoxypropyltrimethoxysilane hydrolysis treatment, drying at 110°C for 10 min, and curing at 140°C for 5 min in step S3, the silane-grafted polyphenylene sulfide coating step was omitted. The long glass fiber forming the siloxane anchoring layer was directly used for subsequent melt lamination, with other conditions remaining unchanged. This comparative example was used to verify the synergistic effect of the siloxane anchoring layer and the silane-grafted polyphenylene sulfide layer.
[0159] Comparative Example 10: Essentially the same as Example 1, except that in step S3, the silane-grafted polyphenylene sulfide was replaced with linear polyphenylene sulfide powder, and the coating was completed at 290°C through fluidized bed contact for 20 seconds, with a coating amount of 0.50 wt%. Other conditions remained unchanged. This comparative example was used to verify the synergistic effect of the siloxane anchoring layer and the silane-grafted polyphenylene sulfide layer.
[0160] Performance testing: Except for Comparative Example 7, which is a part that has not been annealed after injection molding, the other examples and comparative examples are all polyphenylene sulfide parts as described above; the following tests were all conducted under their respective post-treatment conditions.
[0161] After the above-mentioned polyphenylene sulfide parts were prepared as standard notched specimens, they were kept at -40±2℃ for 2 hours. The absorbed energy per unit cross section of the notched specimens was measured by pendulum impact within 5 minutes. Each group consisted of no less than 10 specimens with a thickness of 4mm, a pendulum energy of 2J or 5J, and a consistent notch type. The notched Charpy impact strength, mean ± standard deviation, and failure mode percentage were output to evaluate the cold-resistant high impact capability.
[0162] After preparing dumbbell-shaped specimens according to regulations, the polyphenylene sulfide (PPS) components were conditioned at 23°C and 50%RH. The stress-strain response was recorded at a constant tensile rate, and the tensile strength, modulus, and elongation at break were obtained. Each group consisted of no less than 5 specimens, with uniform tensile rate, gauge length, and specimen type. The tensile strength, tensile modulus, elongation at break, and mean ± standard deviation were output to evaluate the room temperature mechanical load-bearing capacity after interfacial force transfer.
[0163] The aforementioned polyphenylene sulfide (PPS) components were immersed in a 1 mol / L lithium hexafluorophosphate / ethylene carbonate-dimethyl carbonate-ethyl methyl carbonate mixture and a 50 vol% ethylene glycol aqueous solution at 23°C and 85°C, respectively, for a standard evaluation period of 168 hours. For Examples 1, 6, and 7, tensile strength retention was further tested at 0, 72, 168, 336, and 504 hours, with a liquid-to-solid ratio of not less than 20:1. After immersion, the components were cleaned, dried, and retested under the same tensile conditions. Medium penetration caused changes in mass, dimensions, and mechanical properties. The mass change rate, dimensional change rate, and tensile strength retention rate were output to evaluate the stability in typical chemical media of new energy vehicles. Table 1 shows the tensile strength retention results after immersion in an electrolyte solution at 85°C for 168 hours. Figure 16 and Figure 17 The results of the entire process are shown under electrolyte conditions at 85℃.
[0164] After the above-mentioned polyphenylene sulfide parts were prepared into standard strips, they were continuously heated in a silicone oil bath at a specified heating rate under constant bending load, and the temperature corresponding to the specified deflection was recorded. For long glass fiber reinforced systems, the conditions for long fiber reinforced plastics were preferentially applied, with uniform loading stress, heating rate of 2℃ / min and support span. The heat distortion temperature and mean ± standard deviation were output to evaluate the dimensional stability under high temperature load.
[0165] For the above-mentioned polyphenylene sulfide (PPS) parts, 5-10 mg samples were taken and subjected to a heating-cooling-second heating procedure. The melting and crystallization endothermic and exothermic peaks were recorded by differential scanning calorimetry, and the melting enthalpy, crystallization enthalpy, and apparent crystallinity were calculated. The heating and cooling rates, nitrogen flow rates, and the baseline of the second heating were unified. Tm, Tc, ΔHm, ΔHc, and crystallinity were output and expressed as mean ± standard deviation to analyze the influence of annealing and interface design on the crystallization state.
[0166] After washing and drying, the interface-reinforced long glass fibers were fixed by fiber bundle pressing. Surface sampling and layer-by-layer depth analysis were performed using an AlKα source. The changes in elemental composition and Si2p chemical state at different ablation depths reflected the interface hierarchy. The energy transfer, step depth and charging correction methods were unified, and the atomic fraction-depth curve and Si2p peak fitting results were output to verify the gradient interface composed of the siloxane anchoring layer and the silane-grafted polyphenylene sulfide layer.
[0167] To verify the formation of the constructed interface structure and its interlayer transition characteristics, X-ray photoelectron spectroscopy was first used to perform in-depth analysis of Example 1 and related comparative examples. Figure 1The XPS depth profile of Example 1 is shown. X-ray photoelectron spectroscopy depth profiling was performed on the sample from Example 1, and the continuous variation of C1s, O1s, Si2p, and S2p atomic fractions along the depth direction is presented. The results show that the sample surface is rich in organic sulfur-containing components, gradually transitioning to silicon- and oxygen-containing components towards the inner layer. The signal changes of each element in the entire interface region are gradual, without significant abrupt changes, indicating that the fiber surface is not a simple two-phase superposition, but rather forms a gradient interface layer with a continuous transition from the outside to the inside. In contrast, Figure 2 To illustrate the XPS depth profile of Comparative Example 8, X-ray photoelectron spectroscopy depth profiling was performed on the sample to show the changes in the atomic fractions of C1s, O1s, Si2p, and S2p with depth. The elemental composition changes more sharply between the surface and inner layers, and the transition region is significantly shortened. This indicates that without the siloxane anchoring layer, the interface exhibits a more pronounced stratified state, making it difficult to form a continuous compositional gradient. Figure 3 To illustrate the XPS depth profile of Comparative Example 10, X-ray photoelectron spectroscopy depth profiling was performed on the sample to compare the evolution of C1s, O1s, Si2p, and S2p atomic fractions along the depth direction. While a certain transition region was still observable in this sample, its gradient continuity and smoothness were weaker than in Example 1, indicating that the continuity of the interface composition distribution decreases when the outer layer cooperative structure is insufficient. Figures 1 to 3 The comparison shows that in Example 1, a more complete gradient transition structure can be formed between the siloxane anchoring layer and the silane-grafted polyphenylene sulfide layer, which is the basis for achieving stable interface connection.
[0168] After confirming that the interface composition is continuously distributed along the depth direction, the chemical state of the silicon elements at the interface is further analyzed using Si2p narrow-area high-resolution testing to verify whether the interface connection has clear chemical coupling characteristics. Figure 4 The image shows the high-resolution peak fitting diagram of Si2p in Example 1. X-ray photoelectron spectroscopy (XPS) of the sample from Example 1 was used for narrow-region high-resolution Si2p testing and peak separation fitting. The original spectrum, background, overall fitting, and the Si composition of the interface and the substrate are presented. The results show that the peak area of the Si composition at the interface in Example 1 is relatively high, and the overall fitting curve matches the original spectrum well, indicating that a sufficient interfacial chemical connection has been formed between the glass fiber surface and the outer organic phase. Figure 5 To obtain the high-resolution peak fitting diagram of Si2p from Comparative Example 8, X-ray photoelectron spectroscopy (XPS) was performed on the narrow-region Si2p peaks of Comparative Example 8. It can be seen that the substrate SiOx signal is dominant, while the Si component at the interface is significantly weakened. This indicates that the lack of an anchoring layer results in insufficient effective sites for interfacial reactions, leading to a significant decrease in interfacial connectivity. Figure 6To obtain the high-resolution peak fitting diagram of Si2p for Comparative Example 10, X-ray photoelectron spectroscopy (XPS) of the Si2p narrow region of Comparative Example 10 was performed, followed by high-resolution peak separation and fitting. Although this sample still retained some interfacial Si composition, its relative intensity was lower than that of Example 1, indicating that relying solely on local interfacial building blocks is insufficient to establish a high level of interfacial coupling. Furthermore, Figure 7 The scatter plot of the interface Si component area ratio is presented. High-resolution fitting results of Si2p from Samples 1, 8, and 10 were used to statistically analyze the interface Si component area ratio using repeated samples. The statistical results show that Sample 1 exhibits the highest overall interface Si component area ratio and the smallest scatter plot dispersion, indicating that this interface structure not only has a higher degree of connectivity but also better stability among repeated samples. Therefore, the interface reinforcement treatment used in Sample 1 can construct a stable and repeatable chemical bonding layer on the fiber surface, thus providing effective protection for load transfer in subsequent composite processing.
[0169] After verifying the formation and chemical bonding of the interface layer, we further examined its retention capacity under external influences to evaluate the actual stability of the interface structure. Figure 8 To obtain the ATR-FTIR spectra after washing, attenuated total reflectance Fourier transform infrared spectroscopy was performed on samples from Example 1, Comparative Example 9, and Comparative Example 10 after washing. The characteristic absorption signals related to PPS and Si–O–Si were compared. The results showed that Example 1 showed the best absorption signal at 1580 cm⁻¹. - ¹、1472cm - ¹and 1092cm - The presence of clear characteristic peaks near the surface indicates that both polyphenylene sulfide-related structures and silicon-containing network structures still exist on the surface after washing, suggesting that the outer organic phase has not been significantly lost. Figure 9 A scatter plot of the characteristic peak area ratio of PPS / Si–O–Si is presented. ATR-FTIR test results of samples from Example 1, Comparative Example 9, and Comparative Example 10 were used to statistically compare the area ratios of the characteristic peaks of PPS and Si–O–Si. The statistical results show that Example 1 has the highest peak area ratio, indicating that it exhibits the best coexistence of the two components after washing, and the internal and external structures of the interface layer are more intact. Combined with… Figures 1 to 9 It can be considered that the interface constructed by this scheme does not rely solely on physical adhesion, but rather forms a composite interface layer on the glass fiber surface that combines gradient transition, chemical coupling, and washing stability. This provides the necessary prerequisite for the complete retention of the reinforcing phase in subsequent melt processing.
[0170] Based on this, the effects of interface reinforcement treatment on the retention length of long glass fibers and the effectiveness of the reinforcement structure were further investigated. Figure 10The probability density distribution of long glass fiber length is shown in the figure. Statistical analysis of fiber length was performed using samples from Example 1 and Comparative Example 5, and the fiber retention effect was characterized by probability density curves. The results show that the peak position of the fiber length distribution in Example 1 shifts overall towards the longer fiber range, with a significantly higher retention rate in the length range above 0.20 mm. This indicates that the synergistic effect of post-feeding and interface reinforcement can effectively reduce excessive damage to the fibers caused by melt shear. Figure 11 The empirical CDF plot for long glass fiber lengths was generated using samples from Example 1 and Comparative Example 5 for cumulative fiber length distribution analysis. The cumulative distribution curve for Example 1 shifted to the right overall, indicating a higher median fiber length and a lower proportion of short fibers, suggesting that it retains more effective load-bearing fibers after composite processing. Combined with... Figure 10 and Figure 11 It can be seen that this scheme not only improves the interfacial state of the fiber surface, but also helps maintain the aspect ratio advantage of the reinforcing phase. This result is consistent with the aforementioned interfacial layer stability, indicating that the combined effect of a more stable interfacial coating and a milder feeding method helps maintain the structural integrity of the reinforcing phase under 300℃ melt composite conditions.
[0171] The aforementioned fiber retention effect is ultimately reflected in the synergistic improvement of macroscopic mechanical properties. Figure 12 A two-dimensional correlation scatter plot of the impact-tensile strength at -40℃ is presented. Samples from Example 1, Comparative Example 5, and Comparative Example 6 were used to test the notched Charpy impact strength and tensile strength at -40℃, and the two-dimensional correlation is displayed. The results show that the scatter plot of the Sample 1 is mainly distributed in the high impact strength and high tensile strength regions, with the mean point closer to the overall performance balance region. This indicates that the scheme did not sacrifice toughness for strength, nor did it result in a significant loss of stiffness and strength due to improved low-temperature impact performance. In other words, the interface reinforcement layer improves the load transfer efficiency between the fiber and the matrix, while the good fiber retention effect ensures the effective load-bearing length of the reinforcing phase. Both factors contribute to the material maintaining a good strength-toughness balance under low-temperature conditions. This demonstrates that the scheme has good matching between structural design and process path.
[0172] Besides the interface and reinforcing structure, the crystallization state of the matrix also has a significant impact on the overall performance of the part. Therefore, the crystallization behavior after heat treatment is further analyzed. Figure 13 The DSC secondary heating curves were obtained by performing differential scanning calorimetry (DSC) secondary heating tests on samples from Example 1, Comparative Example 7, and Comparative Example 10, comparing the changes in the position and shape of the melting endothermic peak. Example 1 showed a more stable melting peak temperature and a more complete peak shape, indicating that after annealing at 220℃ for 15 min, its crystal structure was more balanced and the degree of crystal region perfection was better. Figure 14To obtain the DSC cooling curves, differential scanning calorimetry (DSC) cooling tests were performed on samples from Example 1, Comparative Example 7, and Comparative Example 10 to compare the differences in the position and intensity of the exothermic crystallization peak. The exothermic crystallization peak of Example 1 was located relatively early and had a more concentrated peak shape, indicating that this sample initiated crystallization more promptly and the crystallization process was more orderly. Figure 15 A scatter plot of apparent crystallinity was generated, and differential scanning calorimetry results from samples of Example 1, Comparative Example 7, and Comparative Example 10 were used to repeatedly analyze the apparent crystallinity. The figure shows that the apparent crystallinity of Example 1 is within the optimal range with minimal fluctuation, indicating that the crystallinity level and repeatability are good after annealing. In summary... Figures 13 to 15 It can be seen that, in Example 1, while maintaining the interface enhancement effect, the matrix crystallization behavior was also effectively controlled, enabling the material to form a more reasonable crystal structure without excessive embrittlement. This result indicates that injection molding at 315℃ combined with annealing at 220℃ for 15 minutes can balance perfect crystallization and structural stability, which has a positive effect on improving the overall performance of the manufactured parts.
[0173] After obtaining a superior interface and crystal structure, the material's ability to retain its performance in an electrolyte environment was further investigated to verify the stability of the structural design under service conditions. Figure 16 The figure shows the process curve of tensile strength retention rate after electrolyte immersion time. Samples from Example 1, Comparative Example 6, and Comparative Example 7 were tested for tensile strength retention rate after electrolyte immersion, and the changes were continuously recorded from 0 h to 504 h. The results show that Example 1 maintained a high tensile strength retention rate throughout the entire immersion period, and the strength decay rate was relatively slow, indicating that its interface layer and matrix structure were more stable in the electrolyte environment. Figure 17 To maintain the area AUC scatter plot, the integral results of the electrolyte immersion retention rate curves of samples from Example 1, Comparative Example 6, and Comparative Example 7 were statistically compared. Example 1 showed the highest area AUC, indicating that it did not only perform well at a single time point but also exhibited superior overall retention capability throughout the entire immersion process. This result corroborates the aforementioned interfacial continuity, chemical coupling degree, and crystal stability, demonstrating that this scheme, through the synergistic construction of a gradient interfacial layer, effective long fiber retention, and a suitable crystal structure, can significantly improve the long-term stability of the material in complex media environments.
[0174] The aforementioned microstructure and performance results are consistent with the macroscopic forming state of the part. Figure 18The image shown is a macroscopic photograph of the polyphenylene sulfide (PPS) component from this embodiment. After melt bonding at 300°C, injection molding at 315°C, and annealing at 220°C for 15 minutes, the sample exhibits a dark brown to brownish-black opaque appearance. The surface is continuous and intact, with regular edges, and no obvious macroscopic cracks, warping, or abnormal shrinkage were observed. These results demonstrate that the PPS composition obtained in this embodiment possesses good molding stability and dimensional retention, meeting the requirements for subsequent structural characterization and mechanical testing. Macroscopically, it also reflects that no significant phase separation or processing instability occurred within the system.
[0175] To further verify the distribution of the reinforcing phase and the interfacial adhesion state from the cross-sectional morphology, the obtained part was observed by scanning electron microscopy. Figure 19 This is a scanning electron microscope image of the cross-section of the polyphenylene sulfide (PPS) component in this embodiment. The sample is a PPS component prepared by a mass ratio of linear PPS resin to interface-reinforced long glass fiber of 85:15. Figure 19 Image a is a low-magnification scanning electron microscope image of the cross-section of the polyphenylene sulfide component in this embodiment. Under low magnification, the polyphenylene sulfide matrix is continuously covered, and no large-area pores or through cracks are seen on the cross-section, indicating that the material has good internal density under the conditions of 300℃ melt composite and vacuum degassing, and the reinforcing phase can be stably embedded in the matrix. Figure 19 Image b is a medium-magnification scanning electron microscope image of the cross-section of the polyphenylene sulfide component in this embodiment. Under medium magnification, long glass fibers with a nominal diameter of 10 μm, their pull-out grooves, and broken ends can be identified. Combined with the fact that the long glass fibers retain a length of about 0.25 mm, it can be seen that the fibers still maintain a certain aspect ratio after composite processing, and can form an effective load-bearing skeleton. Figure 19 Image c is a high-magnification scanning electron microscope (SEM) image of the cross-section of the polyphenylene sulfide (PPS) component in this embodiment. Under high magnification, residual PPS matrix and a relatively continuous interfacial transition zone are visible on the glass fiber surface. No large areas of smooth, exposed surface are observed, indicating strong interfacial adhesion during fiber breakage and pull-out, demonstrating a significant load transfer effect. This result is consistent with... Figures 10 to 12 The observed fiber retention effect and mechanical property improvement are consistent, further proving that the constructed interface structure has a substantial promoting effect on the reinforcing phase.
[0176] Finally, to directly observe the cross-sectional structure of the interface layer, the interface-reinforced long glass fiber was analyzed by transmission electron microscopy. Figure 20This is a bright-field transmission electron microscope (TEM) image of the cross-section of the interface-reinforced long glass fiber in this embodiment. The image shows a clear layered difference between the glass fiber core and the outer cladding layer. The gradient interface layer is continuously distributed along the fiber surface, with an average thickness of approximately 50 nm, indicating that the treatment solution impregnation and subsequent coating processes can form a uniform and continuous interface structure on the fiber surface. Upon magnification, it can be seen that the interface layer gradually transitions from a dense region near the glass fiber surface to the outer organic phase, consistent with the structural characteristics of a gradual distribution from a siloxane anchoring layer to a silane-grafted polyphenylene sulfide layer. This indicates that the interface is a genuinely existing gradient layered structure, rather than a simple abrupt delamination. Combined with… Figures 1 to 20 The test results show that this embodiment achieves a synergistic effect of continuous interface transition, enhanced chemical bonding, effective retention of long fibers, optimized crystallization behavior, and improved media stability by constructing a gradient interface layer with an average thickness of about 50 nm on the surface of long glass fibers and combining it with process conditions of 300℃ melt bonding, 315℃ injection molding, and 220℃ annealing for 15 min. This indicates that the solution has good implementation effect and structural rationality.
[0177] Table 1 Performance of Examples and Comparative Examples As can be seen from the performance of the examples and comparative examples in Table 1, Examples 1-4 are generally superior to the comparative examples in terms of low-temperature impact, mechanical strength, retention rate after immersion in the medium, and heat distortion temperature. Among them, Example 3 exhibits a better low-temperature impact-chemical resistance balance under conditions of medium interface layer thickness, medium coating amount, and medium glass fiber content; Example 2 achieves the highest tensile strength, flexural strength, and heat distortion temperature under conditions of high glass fiber, high coating amount, and high retention length. Comparative Example 5 has the lowest retention length of long glass fibers due to the addition of the main feed, and multiple mechanical properties decrease simultaneously; Comparative Example 6 shows the most significant decrease in immersion retention rate after vacuum degassing; Comparative Examples 8-10 show a simultaneous decrease in low-temperature impact and immersion retention rates after disassembling or replacing the gradient interface layer, indicating that neither a single anchoring layer nor a single coating layer is sufficient to form a stable and effective interface match.
[0178] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and not to limit it. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that any equivalent structural transformations made under the concept of the present invention and using the contents of the specification and drawings of the present invention should be covered within the scope of protection of the claims of the present invention.
Claims
1. A method for preparing cold-resistant, chemically resistant, and high-impact polyphenylene sulfide specifically for new energy vehicles, characterized in that, Includes the following steps: S1. Provides a silane-grafted polyphenylene sulfide, wherein the silane-grafted polyphenylene sulfide is obtained by grafting a linear polyphenylene sulfide resin with vinyltrimethoxysilane in the presence of dicumyl peroxide; S2. Provides 3-glycidoxypropyltrimethoxysilane hydrolysis treatment solution; S3. The commercial long glass fiber is treated with the 3-glycidoxypropyltrimethoxysilane hydrolysis treatment solution described in step S2, and then dried and cured to form a siloxane anchoring layer; then the long glass fiber with the siloxane anchoring layer is brought into contact with the silane-grafted polyphenylene sulfide described in step S1 to form a gradient interface layer on the surface of the commercial long glass fiber, thereby obtaining an interface-reinforced long glass fiber. S4. The linear polyphenylene sulfide resin is directly melt-composite with the interface-reinforced long glass fiber, or the prepreg long glass fiber polyphenylene sulfide granules are first prepared, and then the prepreg long glass fiber polyphenylene sulfide granules are melt-composite with the linear polyphenylene sulfide resin and granulated to obtain a polyphenylene sulfide composition. S5. The polyphenylene sulfide composition obtained in step S4 is injection molded to obtain a polyphenylene sulfide part; In step S2, the 3-glycidoxypropyltrimethoxysilane hydrolysis solution is prepared through the following steps: B1. Mix 3-glycidoxypropyltrimethoxysilane, anhydrous ethanol and deionized water at a mass ratio of 100:300-1000:50-250; B2. Add glacial acetic acid to adjust the pH to 4.0-5.5; B3. Stir at 25-45℃ for 20-90 min to obtain the 3-glycidoxypropyltrimethoxysilane hydrolysis solution; In step S3, the interface-reinforced long glass fiber is prepared through the following steps: C1. The commercially available long glass fiber is brought into contact with the 3-glycidoxypropyltrimethoxysilane hydrolysis treatment solution by spraying or dipping. C2. Dry at 110-140℃ for 10-40 min and cure at 140-170℃ for 5-20 min to form the siloxane anchoring layer; C3. The long glass fiber treated in step C2 is brought into contact with the silane-grafted polyphenylene sulfide at 290-315°C for 20-120 seconds to form the silane-grafted polyphenylene sulfide layer. C4. After cooling, the interface-reinforced long glass fiber is obtained, wherein the gradient interface layer, from the surface of the glass fiber outward, comprises a siloxane anchoring layer formed by the hydrolysis and condensation of 3-glycidoxypropyltrimethoxysilane and a silane-grafted polyphenylene sulfide layer formed by silane grafting polyphenylene sulfide. The thickness of the gradient interface layer is 50-300 nm, the fixation amount of 3-glycidoxypropyltrimethoxysilane is 0.20-1.20 wt%, and the fixation amount is calculated as a percentage of the mass difference between the long glass fiber after forming the siloxane anchoring layer and the long glass fiber before treatment to the mass of the long glass fiber before treatment; the coating amount of silane-grafted polyphenylene sulfide is 0.50-6.00 wt%, and the coating amount is calculated as a percentage of the mass difference between the long glass fiber after forming the silane-grafted polyphenylene sulfide layer and the long glass fiber after forming the siloxane anchoring layer to the mass of the long glass fiber before treatment. In step S4, before preparing the polyphenylene sulfide composition, prepreg long glass fiber polyphenylene sulfide granules are first prepared. The prepreg long glass fiber polyphenylene sulfide granules are prepared through the following steps: D1. The linear polyphenylene sulfide resin is mixed with the interface-reinforced long glass fiber, wherein the linear polyphenylene sulfide resin accounts for 50-85 wt% and the interface-reinforced long glass fiber accounts for 15-50 wt%, with the total mass being 100 wt%; the mixture is melt-composited from the rear section of the barrel via a side-feed method in a twin-screw extruder at 300-320°C, a screw speed of 150-300 r / min, and a residence time of 20-60 s. D2. The discharged material is cooled and granulated, and then dried at 120-140℃ for 2-6 hours to obtain the preimpregnated long glass fiber polyphenylene sulfide granules; In step S4, the interface-reinforced long glass fiber or the pre-impregnated long glass fiber polyphenylene sulfide granules are fed from the rear section of the twin-screw extruder, located in the barrel section from L / 3 to L / 2 from the die head end, via a side-feed method, where L is the total effective length of the twin-screw extruder barrel; The melt bonding conditions in step S4 are as follows: barrel temperature is 300-320℃, screw speed is 150-300r / min, residence time is 20-60s, and vacuum exhaust is used.
2. The preparation method according to claim 1, characterized in that, In step S1, the silane-grafted polyphenylene sulfide is prepared through the following steps: A1. Dry the linear polyphenylene sulfide resin at 120-140℃ for 3-6 hours; A2. The linear polyphenylene sulfide resin dried in step A1, vinyltrimethoxysilane, and dicumyl peroxide are mixed in a mass ratio of 100:0.5-8.0:0.05-1.0; A3. Under nitrogen protection, reactive extrusion is carried out at 290-310℃, screw speed of 100-300 r / min, and residence time of 20-90 s. A4. The extrudate is granulated and dried at 100-120°C for 1-4 hours to obtain the silane-grafted polyphenylene sulfide.
3. The preparation method according to claim 1, characterized in that, In step S3, the nominal diameter of the commercially available long glass fiber is 10-17 μm; the length of the long glass fiber retained in the polyphenylene sulfide part obtained in step S5 is 0.25-0.80 mm.
4. The preparation method according to claim 1, characterized in that, The injection molding conditions in step S5 are: injection molding machine barrel temperature of 315-330℃, mold temperature of 140-160℃, and injection speed of 30-120mm / s.
5. The preparation method according to claim 1, characterized in that, Step S5 is followed by an annealing step, which is performed at 220-240°C for 15-40 minutes.
Citation Information
Patent Citations
Glass fiber reinforced polyphenylene sulfide resin composite material
CN101864169A
Polyphenylene sulfide composite material for high-filling low-warping battery module end plate, and preparation method thereof
CN110776742A
Glass fiber, SiO2 enhanced toughened polyphenylene sulfide material and preparation method thereof
CN103804910A
Glass fiber reinforced polyphenylene sulfide composition as well as preparation method and application thereof
CN114456598A